Antigenicity of Leishmania-Activated C-Kinase Antigen (LACK) in Human Peripheral Blood Mononuclear Cells, and Protective Effect of Prime-Boost Vaccination With pCI-neo-LACK Plus Attenuated LACK-Expressing Vaccinia Viruses in Hamsters - Fernández, Laura; Carrillo, Eugenia; Sánchez-Sampedro, Lucas; Sánchez, Carmen; Ibarra-Meneses, Ana Victoria; Jimenez, Mͣ Angeles; Almeida, Valter dos Anjos; Esteban, Mariano; Moreno, Javier (Frontiers in Immunology, 2018)
Leishmania-activated C-kinase antigen (LACK) is a highly conserved protein among Leishmania species and is considered a viable vaccine candidate for human leishmaniasis. In animal models, prime-boost vaccination with LACK-expressing plasmids plus attenuated vaccinia viruses (modified vaccinia Ankara [MVA] and mutant M65) expressing LACK, has been shown to protect against cutaneous leishmaniasis (CL). Further, LACK demonstrated to induce the production of protective cytokines in patients with active CL or cured visceral leishmaniasis, as well as in asymptomatic individuals from endemic areas. However, whether LACK is capable to trigger cytokine release by peripheral blood mononuclear cells from patients cured of CL due to Leishmania infantum (L. infantum) or induce protection in L. infantum-infected hamsters [visceral leishmaniasis (VL) model], has not yet been analyzed. The present work examines the ex vivo immunogenicity of LACK in cured VL and CL patients, and asymptomatic subjects from an L. infantum area. It also evaluates the vaccine potential of LACK against L. infantum infection in hamsters, in a protocol of priming with plasmid pCI-neo-LACK (DNA-LACK) followed by a booster with the poxvirus vectors MVA-LACK or M65-LACK. LACK-stimulated PBMC from both asymptomatic and cured subjects responded by producing IFN-γ, TNF-α, and granzyme B (Th1-type response). Further, 78% of PBMC samples that responded to soluble Leishmania antigen showed IFN-γ secretion following stimulation with LACK. In hamsters, the protocol of DNA-LACK prime/MVA-LACK or M65-LACK virus boost vaccination significantly reduced the amount of Leishmania DNA in the liver and bone marrow, with no differences recorded between the use of MVA or M65 virus vector options. In summary, the Th1-type and cytotoxic responses elicited by LACK in PBMC from human subjects infected with L. infantum, and the parasite protective effect of prime/boost vaccination in hamsters with DNA-LACK/MVA-LACK and DNA-LACK/M65-LACK, revealed the significance of LACK in activating human and hamster immune responses and support LACK to be a valuable candidate for inclusion in a vaccine against human VL.